Educação em direitos humanos e multiculturalismo: políticas de gênero na educação superior - ANDRADE, Jemina de Araújo Moraes (Instituto Federal do Amapá, 2021)
This study discusses the public policies directed to Human Rights Education (HRE) and multiculturalism, especially the issue of gender in Higher Education. It is a study of a historical character, a qualitative approach, based on the analysis of the discourse. The survey counted as the main source, the National Plan of Education in Human Rights and the National Guidelines for Human Rights Education. The results indicate that the HRE is the way by which it makes possible to recognize its importance, in an attempt to reframe the spaces of teaching, research and extension – the promotion and enhancement of rights, which should be assumed by the universities, however, the issues of gender, even so, present themselves as challenges and tensions regarding the applicability, since the task of the HRE permeates through scientific and ethical commitment, linked to two dimensions that are at the same time, historical and contemporary.